Odpowiedzi

2010-03-21T12:29:28+01:00
A)
4x-3=3x+5
4x-3x=5+3
x=8

b)
5X+2=7-3X
5x+3x=7-2
8x=5 /8
x=⅝

c)
3(x-1)=0
3x-3=0
3x=3 /3
x=1

d)
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 / -6
x=-5

e)
-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-4x= - 15 / -4
x=-15/ -4( ułamek)
x=3¼

f)
4(x-1)=6(x+1)
4x-4= 6x+6
4x-6x=6+4
-2x=10 / -2
x=-5
Najlepsza Odpowiedź!
2010-03-21T12:41:08+01:00
Pisze odrazu rozwiazania:
a)4x-3x=5+3
x=8


b)5x+3x=7-2
8x=5/8
x=0,625 (5/8)

c)3x-3=0
3x=0-3
3x=-3/:3
x=-1

d)
-6x-6=24
-6x=24+6
-6x=30/:-6x
x=5
e) -7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-4x= - 15 / -4
x=-15/ -4( ułamek)
x=3¼


F) 4x-4=6x+6
4x-6x=6+4
-2x=10/-2x
x=8

Mam nadzieje ze chociaz troche pomoglam :) Poozdro :)